2020
DOI: 10.5430/ijhe.v9n2p270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Crime in Nigerian Tertiary Institutions and Administrative

Abstract: This study examined crime in tertiary institutions in southern Nigeria. The purpose of the study was to identify the common crime prevalent in the institution, the administrative strategies for managing crime and find out the extent to which institution managers or Administrators are employing the identified strategies to ensure a crime free environment. Three research questions were asked and answered. The sample of the study was drawn from a population of tertiary institutions in Southern Nigeria A sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…This implies that the implementation of CCTV cameras was low indicating that CCTV cameras were not available in examination venues in Tanzanian universities. The findings were in agreement with the findings by Asiyai and Oghuvbu (2020) which revealed that strategies including the use of CCTV cameras in the examination rooms were lowly implemented in universities. Furthermore, during interviews with the DQAs and the CEOs, the following information was captured.…”
Section: Findings Of the Studysupporting
confidence: 91%
See 2 more Smart Citations
“…This implies that the implementation of CCTV cameras was low indicating that CCTV cameras were not available in examination venues in Tanzanian universities. The findings were in agreement with the findings by Asiyai and Oghuvbu (2020) which revealed that strategies including the use of CCTV cameras in the examination rooms were lowly implemented in universities. Furthermore, during interviews with the DQAs and the CEOs, the following information was captured.…”
Section: Findings Of the Studysupporting
confidence: 91%
“…Consequently, this study collected data through questionnaires, interview guides, document analysis guide and observation guide to triangulate the information to enhance the credibility of the findings. Furthermore, Asiyai and Oghuvbu (2020) investigated the prevalence of crime and the administrative strategies that were used by in Nigeria to address them. The purpose was to identify prevalent crime in HEIs and to find out the degree to which administrative strategies were implemented to curb such crime.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be deduced from the review that amidst the efforts to deal with plagiarism as a menace destroying the fabric covering quality of publications, were constraints to administrative operations among the educational institutions in the sub-region. Largely, the challenges that these institutions encountered while tracing and dealing with plagiarism were institutional capacity-based, including insufficient funding for purchasing software for tracking the frequency of plagiarism, lack of efficient academic library staff, poor implementation of educational policies and unstructured programme for training and re-training of staff to support projects for handling (detecting and reporting) plagiarism cases among academics in the sub-region (Asiyai and Oghuvbu, 2020; Rahayu and Rasto, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When this occurs, mutual interest and reciprocal response define civilised and socially acceptable sexual behaviour. According to Asiyai and Oghuvbu (2019), parents send their children to institutions of higher learning with the hope that they will receive more knowledge, skills and competencies and develop desirable attitudes needed for useful citizenship. It is also hoped that through their education and training in institutions of higher learning, they will become better individuals who can confidently face the challenges of life.…”
Section: Introductionmentioning
confidence: 99%